Antes e depois do trauma: vivência traumática e o mundo presumido - Gregio, Claudia (2005)
Stress is a natural adaptative attempt that mammals use to deal with threatening situations. This process causes series of physiological reactions that happen in cycles that begin and end. However, there are situations where this reaction processes have no end because of stressing agent intensity. It happens in traumatic events that request more time to cope with and adapt to that situation. Living a stressing trauma can cause the development of a Post Traumatic Stress Disorder (PTSD), defined by certain symptoms that persist for more than a month. The PTSD gravity is related to a subjective situation evaluation, which is associated to the personal ability to deal with traumas. This ability is modeled by many factors, including the subjective vision of reality, related to others and to themselves, which is entitled, according to Parkes (1998), Assumptive Worldviews. This concept is based on the Intern Operative Model of Attachment Theory, from John Bowlby, which will be the theoretical base of our analysis. The goal of this work is to study the relation between the Assumptive Worldviews and the Post Traumatic Stress Disorder in individuals submitted to situations defined by themselves as traumatic. The qualitative methodology has been used in order to describe in details and understand the phenomenon using data collected. As tools, two semi-driven interviews were used: one intended to identify how much the individual was affected by the trauma; and the other intended to broach questions related to aspects from Assumptive Worldviews. The traumatic situation chosen is a bus accident that happened in 2004 and the individuals were two women. One of them was present at the accident and the other one was mourning the loss of her father. The data collected were later discussed and analyzed according to Attachment Theory